Kebertahanan Bangunan dengan Adaptif terhadap Lingkungan: Studi Kasus: Makam Syekh Mudzakir Desa Bedono, Kecamatan Sayung, Kabupaten Demak - Mohhamad Kusyanto; Christophorus Koesmartadi; B. Resti Nurhayati (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2023)
Title: The Resilience of Buildings with Adaptability to the Environment (Case Study: Tomb of Syekh Mudzakir in Bedono, Sayung, Demak) Coastal areas have the potential to be affected by abrasion and tidal floods. Syekh Mudzakir's grave is in Tambaksari Subvillage, Bedono Village, Sayung Subdistrict, Demak District, and in the coastal area of the North Coast (Pantura) of Java Island. However, the existence of the tomb and its buildings to this day still survives amidst the marine environment that surrounds it. This tomb has become a religious tourism destination in Demak Regency, with the number of tourists increasing. This research aims to determine and explore the resilience of tomb buildings that are adaptive to abrasion and tidal flood environments. This research is field research. Research data uses primary data and secondary data through the results of observations, interviews, and documentation. The research analysis uses qualitative descriptive analysis. This research shows that Syekh Mudzakir's tomb does not float in the middle of the sea. However, the tomb survives adaptively to the environment by adapting the area, building development, building structural systems, and expanding the site to be robust against abrasion and tidal floods. This research concludes that the family and community survive the grave by adapting to the environment and mitigating disasters that befall the grave area.